Late pleistocene movement of Nam O - Nam Dong fault: evidence from electron spin resonance dating of fault gouge in the Western Da Nang city - Nguyen Quoc, Hung; Tran Thanh, Hai; Vu Anh, Dao; Ngo Xuan, Thanh (Vietnam Journal of Earth Sciences, 2021)
The Nam O - Nam Dong fault is rated as one of the most seismic source zones in Central Vietnam. Field investigation in the mountainous areas in the Cam Le and Hoa Vang districts (Da Nang city), which is a part of the Nam O - Nam Dong fault zone, the authors have discovered fault gouge zone of 5-40 cm width within the Dai Loc granitic rock. Two fault gouge samples were collected for Electron spin resonance (ESR) dating. The results from the ESR dating on the quartz grains from the fault gouge samples showed the youngest age from the smallest fraction, probably indicating that ESR signals in the fractions were completely zeroed at the time of faulting due to frictional heat. The preliminary results from the ESR dating on the quartz grains from the fault gouge indicate that the last major faulting in this site was later the ages of 15.05±3.55 ka to 18.21±4.06 ka ago. Multiple actives during the late Pleistocene - Holocene of this fault had uplifted the fault gouge from a depth-seated to the present-day locality. These data suggest that this fault zone can be classified as a potentially active fault zone and presents some seismic hazards.